Perkembangan Bahasa Pragmatik Pada Anak Attention Deficit Hyperactivity Disorder (ADHD): Kajian Neurolinguistik - Selfia Darmawati; Nuryani Nuryani (Journal of Early Childhood Education (JECE), 2020)
The purpose of this study is to describe the pragmatic development of ADHD childdren. Every child who was born, over time experiencing various development, such as motor development, cognitive development, emotional development, up to language development. Children who have Attention Deficit Hiperactivity Disorder (ADHD) have constraints in some of their development, one of them is pragmatic language development. This research utilizes neurolinguistics theory that explain about language and brain. The result that found in this study are ADHD children can’t survive in a conversation because their focus is easily broken, then they tends to make themselves as a center of a communication. ADHD children also have a difficult in formulating speech and tend to be impulsive and always in a hury. Brain disorder, although not in a language area, still affect the pragmatic language development of ADHD children. By knowing the problem about ADHD children’s pragmatic problem, we can knowing the solution for handle it.